Effectiveness of Start to Run, a 6-week training program for novice runners, on increasing health-enhancing physical activity: a controlled study - Ooms, Linda (BioMed Central, 2013)
BACKGROUND: The use of the organized sports sector as a setting for health-promotion is a relatively new strategy. In the past few years, different countries have been investing resources in the organized sports sector for promoting health-enhancing physical activity. In the Netherlands, National Sports Federations were funded to develop and implement “easily accessible” sporting programs, aimed at the least active population groups. Start to Run, a 6-week training program for novice runners, developed by the Dutch Athletics Organization, is one of these programs. In this study, the effects of Start to Run on health-enhancing physical activity were investigated. METHODS: Physical activity levels of Start to Run participants were assessed by means of the Short QUestionnaire to ASsess Health-enhancing physical activity (SQUASH) at baseline, immediately after completing the program and six months after baseline. A control group, matched for age and sex, was assessed at baseline and after six months. Compliance with the Dutch physical activity guidelines was the primary outcome measure. Secondary outcome measures were the total time spent in physical activity and the time spent in each physical activity intensity category and domain. Changes in physical activity within groups were tested with paired t-tests and McNemar tests. Changes between groups were examined with multiple linear and logistic regression analyses. RESULTS: In the Start to Run group, the percentage of people who met the Dutch Norm for Health-enhancing Physical Activity, Fit-norm and Combi-norm increased significantly, both in the short- and longer-term. In the control group, no significant changes in physical activity were observed. When comparing results between groups, significantly more Start to Run participants compared with control group participants were meeting the Fit-norm and Combi-norm after six months. The differences in physical activity between groups in favor of the Start to Run group could be explained by an increase in the time spent in vigorous-intensity activities and sports activities. CONCLUSIONS: Start to Run positively influences levels of health-enhancing physical activity of participants, both in the short- and longer-term. Based on these results, the use of the organized sports sector as a setting to promote health-enhancing physical activity seems promising.